Regulating illicit trade in natural resources: the role of regional actors in West Africa (2003) - Aning, Emmanuel Kwesi (Capitalism and economic crime in Africa, 2024)
This article explores the multiple efforts that have been initiated by regional actors in West Africa, mainly ECOWAS, 1 to regulate the illicit trade in natural resources in the context of armed conflicts. It then examines the behaviour of ‘spoilers’ who are able to circumvent the sanctions regime and governments’ domestic regulation. The paper argues that the characteristics and multiple dynamics of the armed conflicts in West Africa have created specific opportunities for economic activities in a thriving parallel economy through the ‘illicit’ trade in natural resources.